Ki Enthus Susmono: Skandal Performatif Don Juan dan Kebaruan Gagrag Pedalangan - Hariyanto Hariyanto (Institut Seni Indonesia Yogyakarta, 2019)
This article analyzes Ki Enthus Susmono’s performance through observing some of his previous performances, with the performance idea of Shoshana Felman (2003) in his book, The Scandal of Speaking Body: Don Juan with J.L. Austin, or Seduction in Two Languages, which reads the Don Juan theater by Molière. As a result, it was found that there were similarities between promises by J.L. Austin, Don Juan and Ki Enthus Susmono. Ki Enthus Susmono’s performance has been successfully built through the eclectic, parody and irony representation of postmodern art, which shows the reality of his body’s actions, has been produced repeatedly to produce certain effects so that it becomes a habit (myth). Through his performativity, Ki Enthus Susmono showed his success in building a novel marker of gagrag puppetry. Artikel ini menganalisis performativitas Ki Enthus Susmono melalui pengamatan beberapa rekaman pertunjukannya terdahulu, dengan gagasan performativitas Shoshana Felman (2003) dalam bukunya, The Scandal of The Speaking Body: Don Juan with J.L. Austin, or Seduction in Two Languages, yang membaca teater Don Juan karya Molière. Hasilnya, ditemukan bahwa ada kesamaan antara tindakan janji oleh J.L. Austin,Don Juan dan Ki Enthus Susmono. Performativitas Ki Enthus Susmono berhasil dibangun melalui strategi representasi seni postmodern yang eklektis, parodi, dan ironi, yang menunjukkan realitas tindakan tubuhnya, telah diproduksi berulangkali untuk menghasilkan efek tertentu sehingga menjadi kebiasaan (mitos). Melalui performativitasnya tersebut, Ki Enthus Susmono menunjukkan keberhasilannya membangun penanda kebaruan gagrag pedalangan.